Trends and effectiveness of web-based mathematics learning media in fostering creative thinking in primary education: A systematic review - Nuryami, Nuryami; Cholily, Yus Mochamad; Rahardjanto, Abdulkadir; Effendi, Moh Mahfud; Inganah, Siti (Fakultas Tarbiyah Universitas Ibrahimy, 2025)
This study evaluates the trends and effectiveness of web-based learning media in fostering creative thinking in elementary mathematics education through a Systematic Literature Review (SLR). Data were collected from Scopus and screened using clearly defined inclusion and exclusion criteria based on population, intervention type, study design, and creativity-related outcomes. Of the 36 identified documents, 7 met all criteria and were analyzed. The findings indicate a substantial increase in the use of web-based mathematics media over the last five years, driven by digital transformation and the demand for interactive learning environments. Web-based media were shown to enhance creative thinking through simulations, dynamic visualisations, and contextual problem-solving tasks. However, effectiveness depends on media design, pedagogical strategies, digital infrastructure, and teacher readiness. This review highlights the need for developing creativity-oriented web-based mathematics media that directly support higher-order thinking.